2020
DOI: 10.1038/s41598-020-68739-z
|View full text |Cite|
|
Sign up to set email alerts
|

Divergence in the metabolome between natural aging and Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a progressive and debilitating neurodegenerative disorder and one of the leading causes of death in the United States. Although amyloid plaques and fibrillary tangles are hallmarks of AD, research suggests that pathology associated with AD often begins 20 or more years before symptoms appear. Therefore, it is essential to identify early-stage biomarkers in those at risk for AD and age-related cognitive decline (ARCD) in order to develop preventative treatments. Here, we used an unta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 83 publications
5
10
0
Order By: Relevance
“…A decreased concentration of taurine, a sulfur-containing amino acid that augments the proliferative responses of T-cells, indicates a defect in this process in old mice [63] and points to a reduced potential for detoxification of reactive oxygen species [64]. In line with previous results [65], we observed decreased uridine levels in the ageing spleen, suggesting uridine and taurine as robust spleen-specific biomarker candidates for the ageing process. Accordingly, reduced levels of uridine might be associated with increased cellular senescence in all tissues, as uridine has been shown to affect senescence in human mammary epithelial cells [66].…”
Section: Discussionsupporting
confidence: 91%
“…A decreased concentration of taurine, a sulfur-containing amino acid that augments the proliferative responses of T-cells, indicates a defect in this process in old mice [63] and points to a reduced potential for detoxification of reactive oxygen species [64]. In line with previous results [65], we observed decreased uridine levels in the ageing spleen, suggesting uridine and taurine as robust spleen-specific biomarker candidates for the ageing process. Accordingly, reduced levels of uridine might be associated with increased cellular senescence in all tissues, as uridine has been shown to affect senescence in human mammary epithelial cells [66].…”
Section: Discussionsupporting
confidence: 91%
“…Loss of neuronal function and synapses in the hippocampus, a characteristic of neurodegenerative disorders ( Canchi et al., 2019 ), strongly correlates with cognitive impairment and high levels of Aβ production ( Sheng et al., 2012 ). Other investigators have found evidence of the involvement of many of these pathways, including pathways for axon guidance ( Lee et al., 2019 ) and histidine metabolism ( Hunsberger et al., 2020 ; Smith et al., 2010 ). Neuroinflammation contributes to increased oxidative stress, phosphorylation of tau, reduced Aβ clearance, synaptic degeneration, and neuronal death ( Chen et al., 2016 ; Kempuraj et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with additional epigenetic and microbiome and phenotypic data, the contribution of environmental mixtures on biological systems and aging biology can begin to be explored. For example, in animal models metabolomics has been used to differentiate normative aging from aging related to Alzheimer’s disease ( Hunsberger et al, 2020 ). This same experimental design could be used to better understand the contribution of toxic chemicals in altering the normative aging metabolic profiles and impacts on the Alzheimer’s disease profiles.…”
Section: Integrating the Science Of Aging And Environmental Health Re...mentioning
confidence: 99%